The effect of endograft device on patient outcomes in endovascular repair of ruptured abdominal aortic aneurysms. (December 2017) - Kansal, Vinay; Nagpal, Sudhir; Jetty, Prasad
Objective: Endovascular aneurysm repair for ruptured abdominal aortic aneurysm is being increasingly applied as the intervention of choice. The purpose of this study was to determine whether survival and reintervention rates after ruptured abdominal aortic aneurysm vary between endograft devices. Methods: This cohort study identified all ruptured abdominal aortic aneurysms performed at The Ottawa Hospital from January 1999 to May 2015. Data collected included patient demographics, stability index at presentation, adherence to device instructions for use, endoleaks, reinterventions, and mortality. Kruskal–Wallis test was used to compare outcomes between groups. Mortality outcomes were assessed using Kaplan–Meier survival analysis, and multivariate Cox regression modeling. Results: One thousand sixty endovascular aneurysm repairs were performed using nine unique devices. Ninety-six ruptured abdominal aortic aneurysms were performed using three devices: Cook Zenith ( n = 46), Medtronic Endurant ( n = 33), and Medtronic Talent ( n = 17). The percent of patients presented in unstable or extremis condition was 30.2, which did not differ between devices. Overall 30-day mortality was 18.8%, and was not statistically different between devices ( p = 0.16), although Medtronic Talent had markedly higher mortality (35.3%) than Cook Zenith (15.2%) and Medtronic Endurant (15.2%). AUI configuration was associated with increased 30-day mortality (33.3% vs. 12.1%, p = 0.02). Long-term mortality and graft-related reintervention rates at 30 days and 5 years were similar between devices. Instructions for use adherence was similar across devices, but differed between the ruptured abdominal aortic aneurysm and elective endovascular aneurysm repair cohorts (47.7% vs. 79.0%, p < 0.01). Notably, two patients who received Medtronic Talent grafts underwent open conversion >30 days post-endovascular aneurysm repair ( p = 0.01). Type 1 endoleak rates differed significantly across devices (Cook Zenith 0.0%, Medtronic Endurant 18.2%, Medtronic Talent 17.6%, p = 0.01). Conclusion: Although we identified device-related differences in endoleak rates, there were no significant differences in reintervention rates or mortality outcomes. Favorable outcomes of Cook Zenith and Medtronic Endurant over Medtronic Talent reflect advances in endograft technology and improvements in operator experience over time. Results support selection of endograft by operator preference for ruptured abdominal aortic aneurysm.